CUSTOMER SATISFACTION AT SWISS-BELRESIDENCES KALIBATA JAKARTA - Dino Leonandri; Rina Fitriana (Integrated Journal of Business and Economics (IJBE), 2020)
The competition between one hotel and another has made each hotel strategize to keep their customers. It also happens in the Swiss-Belresidences Hotel Kalibata Jakarta. Among several factors influencing customer loyalty is the quality of service and product quality. This research intends to find out the influence of service quality (X1) and product quality (X2) on customer satisfaction. Respondents in this study were 100 guests staying at the Hotel Swissbel Residence Kalibata Jakarta. Primary Data is taken using questionnaires with simple random sampling techniques and processed using SPSS. Test result on correlation between service quality variable and customer satisfaction variable shows the number of 0.498 which means service quality has a moderate influence on customer satisfaction. Meanwhile result test correlation between product quality variables and customer satisfaction variables is 0.700 that shows how product quality (X2) has a strong influence on customer satisfaction (Y). Coefficient determination test results in 51.5% which explains what both variable service quality (X1) and product quality (X2) affect the customer satisfaction variable (Y) of 51.5% and the remaining 48.5% is influenced by other factors or variables that are not included in the the research.